ECTOPARASITES OF DOGS AND CATS (SPREADING AND TREATMENT) - Kruchynenko, O. V. (Scientific Progress & Innovations, 2020)
Data concerning relatively most widespread causative agents of dog and cat ectoparasitic diseases (Canis lupus familiaris & Felis catus Linnaeus, 1758) have been given in the article. They are of interest to doctors of veterinary medicine. Chemical-therapeutical preparations, which are available in the world pharmaceutical market and used with the aim of treatment and prevention of such dog and cat diseases, have been presented. The main pathogens of dog and cat ectoparasitic diseases have been considered taking into account modern systematic parasites’ condition. The peculiarities of ectoparasites’ spreading on the territory of Ukraine and the world have briefly been presented according with the data of well-known scholars in veterinary parasitology. Information as to peculiarities of using insect-acaricidal preparations in case of animal infestation with ticks and insects has been generalized. Data about the most widely spread preparations and chemical compounds, which are active substances of these preparations (their chemical names in different counties of the world, also the synonyms and main pharmacological properties), have been given in the paper. The information has been proosed concerning dosages and peculiarities of using insect-acaricidal preparations in case of ectoparasitic diseases of dogs and cats according to the data of modern scientific literature and corresponding recommendations as to their practical application. While reviewing, it has been revealed that cats are most often infected with O.cynotis. Young animals are most susceptible to otodectic mange. The peak of invasion on the territory of Ukraine is observed in winter period. It has been found that dogs are more susceptible to ctenocefalosis and demodicosis. Dogs are also more often attacked by ixodids. The aim of the work was to show modern state concerning ectoparasitic diseases of dogs and cats both on the territory of Ukraine and in the world, single out the existing insect-acaricidal preparations, generalize the information as to their application. It has been established that preparations based on fipronil, and permethrin or selamectin are most often used for the treatment and prevention of dog and cat ectoparasitoses. In case of acariases, ivermectin remains the effective preparation. The conducted analysis of literature sources will enable to supplement the available data concerning the spreading, prevention, and treatment of dogs’ and cats’ ectoparasitoses. The data presented in the article will help specialists of veterinary medicine choose effective insect-acaricide. At the same time, the given information will help ensure veterinary wellbeing of dogs and cats in Ukraine.